Culture wars : opposing viewpoints - Whitehead, Fred. (San Diego, CA : Greenhaven Press, 1994)
Presents opposing viewpoints on issues related to cultural diversity, American education, cultural values, and the decay of American culture.
Includes bibliographical references and index.
Keywords: Cultural pluralism -- United States; Multiculturalism -- United States; Culture conflict -- United States; Multiculturalism; United States -- Civilization